Intervención de enfermería para disminuir la incidencia de casos de LEISHMANIA en la parroquia Puerto Limón, cantón Santo Domingo, Provincia Santo Domingo de los Tsáchilas. - Vinces Rezabala, Julia Edith (2014)
The real objective of this investigation topic was to establish the Incidence of cases of leishmania, in the Parish Port Lemon of the Sacred Canton Domingo in the year 2014 and the profile in that it acts in the state of all the individuals' well-being, family and the community. This investigation work was carried out from an analytic, descriptive, synthetic and deductive point of view, for what toiled in the place to process the current investigation where he/she originates the investigation, this it is the Parish Port Lemon of the Sacred Canton Domingo, with the purpose of reaching the whole investigation of unequivocal sources. This way the investigation the Incidence of cases of leishmania; and the obtaining of the most important causes that problematizan the same one. In the investigation you could conclude the necessity to be the so much of the main causes of the Incidence of cases of leishmania, in the Parish Port Lemon of the Sacred Canton Domingo in the year 2014, to the entirety of the services that toasts in the epidemic field. .